Microwave Induced Improved Synthesis of Some Novel Substituted 1, 3-Diarylpropenones and their Antimicrobial Activity - K. L. Ameta; Biresh Kumar; Nitu S. Rathore (E-Journal of Chemistry)
Application of solid support, solvent free reaction condition and a dynamic microwave power system in the chemical synthesis of some novel 1, 3-diaryl-propenones has been described. A series of chalcones (3a-h) were synthesized by the condensation of 4-hydroxy-3,5-dinitroacetophenone with various substituted aromatic aldehydes in presence of montmorrilonite K10 as a catalyst and solid support media under microwave irradiation. The protocol offers several advantages such as simple procedure, fast reaction rate, mild reaction condition, eco-friendly and improved yield as compared to conventional methods. These compounds have been screened for their antibacterial and antifungal activities against different microorganisms. The structures of novel synthesized compounds have been established on the basis of elemental analysis, 1H NMR, 13C NMR and IR spectral data.